Prognostic role of left ventricular diastolic function assessed by speckle tracking echocardiography in patients after surgical ventricular repair. (25th November 2020) - Nemchyna, O; Solowjowa, N; Dandel, M; Hrytsyna, Y; Stein, J; Soltani, S; Knierim, J; Schoenrath, F; Falk, V; Knosalla, C
Abstract: Background: Assessment of left ventricular (LV) diastolic function brings important prognostic information for patients with heart failure and could be evaluated by speckle tracking echocardiography (STE). Less known about its role in patients planned for surgical ventricular repair due to LV aneurysm. Purpose: The aim of this study was to evaluate the prognostic role of STE parameters of LV diastolic function for prediction of all-cause mortality in patients after surgical ventricular repair. Methods: We retrospectively evaluated data of 163 consecutive pts (mean age 62.3±11.5 years, 74.8% males) with anteroapical LV aneurysm who underwent surgical ventricular repair combined with coronary artery bypass surgery (71.8%) Prognostic role for prediction of all-cause mortality was assessed for various STE parameters, including left atrial strain (LAS) measured as peak reservoir strain and for the ratio of early to late global longitudinal strain rate (GLSRe/GLSRa). Results: During a median follow-up of 4.7 years (IQR: 1.6–8.9 years) there were 65 deaths, 5 year survival rate was 73.8 (95% CI 67–79%). Baseline ejection fraction, end-diastolic and end-systolic volumes of LV did not differ between pts who died and survived at 5 year after the surgery, whereas LAS was significantly higher and GLSRe/GLSRa was significantly lower in survivors. Cox proportional hazard model adjusted to demographic and clinical variables demonstrated that LAS and GLSRe/GLSRa were independent predictors of all-cause death, with HR of 0.79 (95% CI 0.66–0.95, p=0.012) for each 5% increase of LAS and HR of 1.24 (95% CI 1.1–1.4, p=0.001) for each 0.5 increase of GLSRe/GLSRa. Moreover, GLSRe/GLSRa remained an independent predictor after additional adjustment for LV end-systolic volume, sphericity index and presence of mitral insufficiency of grade 2 and higher. A significant difference in median survival time was demonstrated according to the following cut-offs: LAS ≥16.7% (12.1 vs. 6.4 years, p=0.01), GLSRe/GLSRa ratio ≥2.3 (3.3 years vs. 10.2 years, p=0.0005) (Figure). The classification and regression tree analysis with the application of all two-dimensional, Doppler and various speckle-tracking echocardiographic parameters revealed that GLSRe/GLSRa and LAS were the most important echocardiographic variables for risk stratification for 5-year mortality. Conclusion: This study demonstrates that STE parameters of LV diastolic function are important predictors of all-cause mortality after surgical ventricular repair due to anteroapical aneurysm of LV and could be used in the preoperative decision-making process. Funding Acknowledgement: Type of funding source: None